The Cost of Equity Capital: A Reconsideration: Discussion - Crockett, Jean (Journal of Finance, 1978)
Jean Crockett, The Cost of Equity Capital: A Reconsideration: Discussion, The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 878-881